Indicators of Equity and Access in Formative Assessment Practices: Student Perspectives - Amini, Shokoofeh (Assessment and Practice in Educational Sciences, 2024)
This study aims to identify indicators of equity and access in formative assessment practices from the perspectives of students in Tehran. A qualitative research design was employed, utilizing semi-structured interviews with 25 students from various educational institutions in Tehran. Participants were purposefully sampled to ensure diversity in backgrounds and academic experiences. Data collection continued until theoretical saturation was reached. All interviews were audio-recorded, transcribed verbatim, and analyzed thematically using NVivo software. The analysis followed Braun and Clarke’s (2006) guidelines, with open coding and the development of themes and subthemes reflecting students’ experiences and perceptions related to equity and access in formative assessment. Analysis of the interview data revealed three main themes: fairness and transparency, accessibility and support, and inclusivity and student voice. Students emphasized the importance of clear assessment criteria, unbiased feedback, and consistent grading as foundational to fair assessment. Accessibility was highlighted through the need for language support, digital equity, and individualized accommodations, while emotional and academic supports were also noted as crucial. Inclusivity emerged in students’ calls for culturally sensitive practices, active mechanisms for student feedback, adaptation to learning styles, and opportunities for peer collaboration. Participants provided specific examples of how these indicators influenced their sense of fairness and engagement in formative assessment tasks. The study underscores the centrality of student perspectives in identifying practical indicators of equity and access within formative assessment. Findings highlight the necessity of transparent criteria, accessible resources, and inclusive practices to ensure that all students can meaningfully participate and benefit from formative assessment. The results provide actionable insights for educators and policymakers committed to fostering more equitable and supportive assessment environments in diverse educational contexts.